2015
DOI: 10.1007/978-3-319-17121-0_59
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Cyclic Light Preconditioning Protect Against Light-Induced Retinal Degeneration and Evoke Similar Gene Expression Patterns

Abstract: To compare patterns of gene expression following preconditioning cyclic light rearing versus preconditioning aerobic exercise. BALB/C mice were preconditioned either by rearing in 800 lx 12:12 h cyclic light for 8 days or by running on treadmills for 9 days, exposed to toxic levels of light to cause light-induced retinal degeneration (LIRD), then sacrificed and retinal tissue harvested. Subsets of mice were maintained for an additional 2 weeks and for assessment of retinal function by electroretinogram (ERG). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
(30 reference statements)
1
9
0
1
Order By: Relevance
“…Exercise shows promise as an intervention for retinal degenerative disease, but many questions remain about the nature of its protective effects. Consistent with previous studies,1214,16,17,41,42 we confirmed that exercise protects retinal function in a retinal degeneration model. We advanced these findings by demonstrating that higher intensity exercise may not provide more benefit to retinal function after LIRD, potentially because of the increased stress as reflected by increased circulating corticosterone levels.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Exercise shows promise as an intervention for retinal degenerative disease, but many questions remain about the nature of its protective effects. Consistent with previous studies,1214,16,17,41,42 we confirmed that exercise protects retinal function in a retinal degeneration model. We advanced these findings by demonstrating that higher intensity exercise may not provide more benefit to retinal function after LIRD, potentially because of the increased stress as reflected by increased circulating corticosterone levels.…”
Section: Discussionsupporting
confidence: 93%
“…Although the 10 m/min treadmill exercise regimens have previously been shown to protect against LIRD,17,42 it was not known if lower intensity exercise would be beneficial. One exciting application for this lower intensity but equally effective exercise treatment is for those suffering from age-related retinal degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…; Chrenek et al. ). Voluntary exercise using running wheel for 6 weeks was also suggested to protect photoreceptor in the retinitis pigmentosa model in mice (Hanif et al.…”
Section: Neuroprotection Of Physical Exercise In Glaucomamentioning
confidence: 98%
“…In diabetic retinopathy, exercise on the treadmill for 30 min/day, 5 days/week for 6 weeks was found to ameliorate diabetes-induced apoptosis in retinal cells (human or animal model) (Kim et al 2013). After 4 weeks of exercise (preconditioning of exercise for 2 weeks and additional 2 weeks of exercise after light exposure) at intensity of 10 metres/min, at a frequency of 5 days/ week, 60 min/day, was found to be effective in preserving function and count of photoreceptors in lightinduced retinal degenerative models in mice (Lawson et al 2014;Chrenek et al 2016). Voluntary exercise using running wheel for 6 weeks was also suggested to protect photoreceptor in the retinitis pigmentosa model in mice (Hanif et al 2015).…”
Section: Neuroprotection Of Physical Exercise In Glaucomamentioning
confidence: 99%
“…Regular general physical exercise is not only a part of healthy life style, but also a rehabilitation strategy showing neuroprotective effects in numerous diseases. Recently, exercise has been proven to be neuroprotective in animal models of retinal degeneration [85][86][87]. Wild-type BALB/c mice were forced to exercise for 5 days/ week for 2 weeks before being exposed to bright light.…”
Section: Studies In Animal Modelsmentioning
confidence: 99%